PARADIGMATIS FENOMENOLOGI DALAM ILMU KOMUNIKASI (Studi Konstruksi Makna Realitas Media dan Komunikasi) - Ahmad Toni; Rini Lestari (Universitas Bunda Mulia, 2013)
Paradigmatic phenomenological interpretation of the reality is trying to trace the process of media and communications that are the essence of reality, not reality itself on engineering. Phenomenology as the study puts the study of communication in matters transcendental deity diterpakan by the media. Phenomenology based on the values of humanity as well as media that high menunjung Human Rights so that it can be done with hermenutik approach.Phenomenology seeks to reveal the truth of the human senses as an empirical truth that is based on media exposure and other communication patterns.Keywords: paradigmatic, phenomenology, construction, media, communicationreality